1999
DOI: 10.1055/s-1999-14043
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity of Extracts and Alkaloids of Three Alstonia Species from Thailand

Abstract: Methanol extracts prepared from various parts of Alstonia scholaris, A. macrophylla and A. glaucescens, collected from Thailand, have been assessed for antiplasmodial activity against multidrug-resistant K1 strain of Plasmodium falciparum cultured in human erythrocytes. Pronounced antiplasmodial activity was exhibited by methanol extract of the root bark of A. macrophylla with an IC50 value of 5.7 micrograms/ml. Thirteen indole alkaloids were isolated from the active extract. These alkaloids and a semisyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 0 publications
2
111
0
1
Order By: Relevance
“…Differences in the biology of CQR P. falciparum strains and the CQS P. berghei strain used in that study were considered to explain the negative in vivo result, since it had been shown that this alkaloid was essentially active against CQR strains of P. falciparum, and a CQS P. berghei strain was used in that study (Frederich et al 1999). villalstonine and macrocarpamine were the most active against the CQR K1 strain in vitro (IC 50 270 and 360 nM, respectively) (Wright et al 1993, Keawpradub et al 1999. Voacamine, isolated from Tabenamontana fuchsiaefolia A. DC.…”
Section: Alkaloids: New Leads For Antimalarial Drugs?mentioning
confidence: 99%
“…Differences in the biology of CQR P. falciparum strains and the CQS P. berghei strain used in that study were considered to explain the negative in vivo result, since it had been shown that this alkaloid was essentially active against CQR strains of P. falciparum, and a CQS P. berghei strain was used in that study (Frederich et al 1999). villalstonine and macrocarpamine were the most active against the CQR K1 strain in vitro (IC 50 270 and 360 nM, respectively) (Wright et al 1993, Keawpradub et al 1999. Voacamine, isolated from Tabenamontana fuchsiaefolia A. DC.…”
Section: Alkaloids: New Leads For Antimalarial Drugs?mentioning
confidence: 99%
“…Substituted indoles have been referred to as "privileged structures" since they are capable of binding to many receptors with high affinity [1]. Cycloocta [b]indoles, an emerging class of biologically relevant indole analogues that has been found in many naturally occurring alkaloids such as macroline, ajmaline, macrocarpamine, villalstonine, O-acetyl macralstonine and macralstonine ( Figure 1) and known to exhibit wide range of pharmacological properties such as antiamoebic, antiplasmodic, antiprotozol and antihypertensive activities [2][3][4][5]. The cycloocta [b] indole framework has recently been a subject of biology-oriented synthesis (BIOS) [6] and their analogues are promising targets for developing a novel class of potent and selective Mycobacterium protein tyrosine phosphatase B (MptpB) inhibitors against Mycobacterium tuberculosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 The other medicinal plants that have been used as antimalarial agents in Indonesia are Carica papaya, 6 Phyllantus niruri, 7 and Alstonea scolaris. 8 C. bicolor PF Stevens or Bintagor is one of the species of genus Calophyllum (Clusiaceae family) that traditionally used as a treatment of various diseases. 9 Calophyllum has 180-200 species that grow in the coastal areas in Kalimantan and Papua.…”
Section: Introductionmentioning
confidence: 99%